Scientific and technical fundamentals for explosive destruction of the mass composed of rocks with different hardness - Zairov, Sh.; Ravshanova, M.; Karimov, Sh. (Розробка родовищ, 2017)
Purpose. To develop the technology for explosive destruction of solid inclusions in the mass of rocks with different hardness on the basis of established correlations between changes in the radius of hard streaks fragmenting, fracturing density and relative distance to the free surface during various initiating techniques in rocks of different hardness. Findings. The developed technology for explosive destruction of mass of rocks with different hardness was implemented in the Tashkura quarry of Dzheroj-Sardara phosphate deposit of Navoiy MMC resulting in the economic effect of UZS 581.7 mln per 10.5 mln m³ of the extracted rock, while the economic effect in the free industrial and economic zone “Navoiy” was more than UZS 12 mln per 17000 m³ of the extracted rock. Мета. Розробка способу вибухового руйнування міцних включень в масиві різноміцних гірських порід на основі встановлення закономірностей зміни радіуса дроблення міцних пропластков та щільності тріщиноутворення від відносної відстані до вільної поверхні при різних способах ініціювання в різноміцних гірських породах. Результати. Розроблені способи вибухового руйнування масиву різноміцних гірських порід впроваджені на кар’єрі Ташкура Джером-Сардарінского родовища фосфоритів Навоїйського гірничо-металургійного комбінату з отриманням економічного ефекту в розмірі 581.7 млн UZS на 10.5 млн м³ відбиваної гірської маси й у вільній індустріально-економічній зоні “Навої” з отриманням економічного ефекту в розмірі понад 12 млн UZS на 17000 м³ відбиваної гірської маси. Цель. Разработка способа взрывного разрушения крепких включений в массиве разнопрочных горных пород на основе установления закономерностей изменение радиуса дробления крепких пропластков и плотности трещинообразования от относительного расстояния до свободной поверхности при различных способах инициирования в разнопрочных горных породах. Результаты. Разработанные способы взрывного разрушения массива разнопрочных горных пород внедрены на карьере Ташкура Джерой-Сардаринского месторождения фосфоритов Навоийского горно-металлургического комбината с получением экономического эффекта в размере 581.7 млн UZS на 10.5 млн м³ отбиваемой горной массы и в свободной индустриально-экономической зоне “Навоий” с получением экономического эффекта в размере более 12 млн UZS на 17000 м³ отбиваемой горной массы.